Dwelling and new ruralities : collective artistic research in a design studio at Lund School of Architecture (2021–2025) - Mateo Muñoz, Jesus ; 0009-0007-0379-110X (Institutionen för arkitektur, Lunds universitet, 2026)
This publication presents a collective investigation into contemporary rural transformation developed through a series of design studios at Lund School of Architecture between 2021 and 2025. Focusing on the notion of “new ruralities,” the work explores how changing relationships between habitation, work, mobility, technology, and ecology are reshaping conditions of dwelling in the countryside. The research is conducted through architectural design, using speculative proposals to examine and articulate emerging spatial, social, and environmental configurations. Two contexts in southern Sweden: the village of Grönby and Ladugårdsmarken in the outskirts of Lund, that serve as sites of inquiry, offering contrasting conditions through which these developments can be explored. Rather than advancing a single model, the publication assembles a diverse set of projects that together construct a field of investigation. Each proposal addresses specific aspects of rural change, contributing to a broader understanding of how rural life is being redefined. In doing so, it demonstrates how architectural design can make perceptible emerging conditions that are not yet fully defined.
Keywords: Rural dwelling; New rurality; Architectural design; Artistic research; Rural transformation